ADAR1 promotes systemic sclerosis via modulating classic macrophage activation - Sun, Chenming; Cai, Dunpeng; Chen, Shi-You (Frontiers in Immunology, 2022)
As a multisystem autoimmune disorder disease, systemic sclerosis (SSc) is characterized by inflammation and fibrosis in the skin and other internal organs. However, mechanisms underlying the inﬂammatory response that drives the development of SSc remain largely unknown. In this study, we discover that adenosine deaminase acting on RNA (ADAR1), a deaminase converting adenosine to inosine (i.e., RNA editing) in RNA, is abundantly expressed in macrophages in the early stage of bleomycin-induced SSc. Importantly, ADAR1 is essential for SSc formation and indispensable for classical macrophage activation because ADAR1 deficiency in macrophages significantly ameliorates skin and lung sclerosis and inhibits the expression of inﬂammation mediator inducible NO synthase (iNOS) and IL-1β in macrophages. Mechanistically, deletion of ADAR1 blocks macrophage activation through diminishing NF-κB signaling. Taken together, our studies reveal that ADAR1 promotes macrophage activation in the onset of SSc. Thus, targeting ADAR1 could be a potential novel therapeutic strategy for treating sclerosis formation.